2006
DOI: 10.1177/1076029606291382
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein in Hypertensive Disorders in Pregnancy

Abstract: Hypertension is the most frequent medical complication of pregnancy. A recent report demonstrates the flogistic pathogenesis of pregnancy-induced hypertension. Because C-reactive protein (CRP) is a marker of inflammation, it can be used in the differential diagnosis of hypertensive disorders of pregnancy. A total of 322 pregnant women at 24 to 32 weeks' gestation were enrolled. The control group (A) comprised 190 women. Sixty-three women had preeclampsia (PE, group B), 31 women presented transient hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
8
24
2
2
Order By: Relevance
“…1) regression analysis showed that CRP had significant negative correlation with birth weight (birth weight: r= -0.367; p<0.05) . Age range of pre-eclamptic patient are similar in other studies 15,16 like ours.…”
Section: Resultssupporting
confidence: 74%
“…1) regression analysis showed that CRP had significant negative correlation with birth weight (birth weight: r= -0.367; p<0.05) . Age range of pre-eclamptic patient are similar in other studies 15,16 like ours.…”
Section: Resultssupporting
confidence: 74%
“…The differences in results might be due to small size (n ¼ 6 women) and heterogeneity of the preeclampsia group in Fleming's study. Neither did we find statistical difference in CRP levels between normal pregnancy and preeclampsia, although other previously found higher levels of CRP in preeclampsia [43].…”
Section: Discussioncontrasting
confidence: 61%
“…42 We showed earlier that Ang II increases CRP in a model of target-organ damage. 43 Shagdarsuren et al 44 showed recently that human CRP contributes to cardiovascular disease and that the effect can be abrogated by a small molecule inhibitor of CRP. Conceivably, such a molecule could be useful to clinically explore in preeclamptic patients.…”
Section: Discussionmentioning
confidence: 99%